ضوابط الانفتاح الحضاري في المجتمع المسلم - مصطفاوي لزهر (University of Eloued جامعة الوادي, 2024)
"ملخص الدراسة:‏ تهدف الدّراسة الى بيان ضوابط الانفتاح الحضاري في المجتمع المسلم، ‏و بناء على ما ‏سبق تتحدد مشكلة الدراسة في السؤال الرئيس التّالي:‏ ما هي ضوابط الانفتاح الحضاري في المجتمع المسلم ؟ .‏ وينبثق عن هذا السؤال الرئيس عدة أسئلة فرعية؟. ‏  ما هو مفهوم الانفتاح الحضاري؟  ما هي أهم مرتكزات عملية الانفتاح الحضاري؟  ما أهم ضوابط الانفتاح الحضاري في المجتمع المسلم ؟  كيف نفعّل دور وسائط التربية الإسلامية في ضبط عملية الانفتاح ؟ ولقد استخدمت في هذه الدراسة المنهج الاستقرائي والمنهج الوصفي، وذلك بهدف ‏استقراء أهم أقوال العلماء والمفكرين حول الموضوع، كما تستخدم الدراسة المنهج التحليلي ‏والمنهج النقدي، من خلال منهج تكاملي تستفيد منه الدراسة في مباحثها كافة.‏ ولقد توصلنا إلى النتائج التالية :‏  الانفتاح الحضاري في المجتمع المسلم: عملية ذات أسس منضبطة للتواصل والتفاعل ‏الإنساني.‏  من أبرز ضوابط الانفتاح الحضاري وهي أن يكون: بعد الفهم العميق للعلم الشرعي ، ‏وخالياً من عقدة الانبهار بالآخر مع الاحتفاظ بروح العزة في الانتماء للدين ‏الإسلامي.‏  من أهم مرتكزات عملية الانفتاح المنضبط: إدراك معنى الأخوة الإنسانية التي وضعها ‏القرآن الكريم، وقبول التعددية، وإقرار الإسلام لحرية التدين.‏ "Abstract The study aims to clarify the controls of civilized openness in ‎Muslim society, and based on the above, the problem of the study is ‎determined in the following main question‏.‏ What are the controls for civilized openness in Muslim ‎society? ‎ ‏‎ Several sub-questions emerge from this main question?.‎ ‎1.‎ What is the concept of civilized openness?‎‏ ‎2.‎ What are the most important foundations of the process of ‎civilized openness?‎ ‎3.‎ What are the most important controls for civilized openness ‎in Muslim society from an Islamic perspective?‎ ‎4.‎ How do we activate the role of Islamic education media in ‎controlling the process of openness civilized?‎ In this study, I used the inductive method and the descriptive ‎method.‎ We have reached the following results:‎ ‎1.‎ Openness:a process with disciplined foundations for ‎communication and human interaction, give and take.‎ ‎2.‎ One of the most prominent controls for civilized openness is that ‎it must have a deep understanding of Islamic law, and be free ‎from the complex of fascination with others.While maintaining the ‎spirit of pride in belonging to the Islamic religion.‎ ‎3.‎ Among the most important foundations of the process of ‎controlled openness: realizing the meaning of human ‎brotherhood through the teleology set forth by the Holy Qur’an, ‎accepting pluralism in human societies,’s recognition of freedom ‎of religion.‎
Keywords: الانفتاح - الحضارة - الانفتاح الحضاري.‏; ‎ Openness - Civilization - Civilized openness ‎.‎